2022
DOI: 10.1111/papt.12433
|View full text |Cite
|
Sign up to set email alerts
|

“If there is a tension about something, I can solve it”: A qualitative investigation of change processes in a trial of brief problem‐solving interventions for common adolescent mental health problems in India

Abstract: Vikram and Michelson, Daniel (2022) "If there is a tension about something, I can solve it": a qualitative investigation of change processes in a trial of brief problem-solving interventions for common adolescent mental health problems in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…Each module to last 30-60 minutes. Coaching sessions to last 20-30 minutes Previous research also provides confidence that brief interventions can help reduce mental health difficulties in children (Malik et al, 2022). A recent meta-analysis (Schleider & Weisz, 2017) and review (Schleider et al, 2019) demonstrated that even single session interventions (SSIs) produce significant benefits for youth mental health difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Each module to last 30-60 minutes. Coaching sessions to last 20-30 minutes Previous research also provides confidence that brief interventions can help reduce mental health difficulties in children (Malik et al, 2022). A recent meta-analysis (Schleider & Weisz, 2017) and review (Schleider et al, 2019) demonstrated that even single session interventions (SSIs) produce significant benefits for youth mental health difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…The PRemIum for aDolEscents (PRIDE) Study manualized PST was chosen as the specific PST package to adapt (Michelson et al, 2020 ). The PRIDE study designed and evaluated this brief lay-counselor delivered PST intervention for adolescent students in India (Chorpita et al, 2020 ; Malik et al, 2022 , 2023 ; Please see the PRIDE website for full details: http://sangath.in/pride/ ). PRIDE PST is 5-sessions.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies in India aimed to evaluate interventions to improve adolescent mental health in India. Remote online interventions had limited acceptability, a school-based mixed-gender body image intervention with a trained psychologist resulted in sustained improvements in many areas,20 and teaching of problem solving skills by a lay counsellor resulted in such skills being sustained and generalised beyond the original presenting problems 21…”
mentioning
confidence: 99%